1993
DOI: 10.1159/000168618
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead in Hemodialysis Patients

Abstract: Blood lead corrected for hematocrit (PbC) was measured in 115 hemodialysis (HD) patients. Information was collected with a questionnaire about personal and environmental factors thought to influence blood Pb levels. HD patients had significantly higher mean blood Pb than healthy subjects (p < 0.001). A non-negligible percentage of the HD population (13%) had values over 30 µg/ dl, the threshold for risk in occupational exposure, and 4% over 40 µg/dl which reflects Pb intoxication. No association was found betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The median blood lead level in the study subjects was 7.3 µg/dL (0.1, 29.9 µg/dL) which was higher than the level of 5.8 µg/dL [1.6, 19.1 µg/dL] in patients with chronic kidney disease and than the level of 4.8 µg/dL [1.6, 33.6 µg/dL] in stroke patients with normal serum creatinine levels in Taiwan [5,11,12]. Colleoni N et al and Kessler M et al, demonstrated elevated blood lead levels in patients who were on chronic renal dialysis [13,14]. A study which was done by Muntner P et al, demonstrated that there was an association between the blood lead level and the bone lead concentrations [15].…”
Section: Discussionmentioning
confidence: 92%
“…The median blood lead level in the study subjects was 7.3 µg/dL (0.1, 29.9 µg/dL) which was higher than the level of 5.8 µg/dL [1.6, 19.1 µg/dL] in patients with chronic kidney disease and than the level of 4.8 µg/dL [1.6, 33.6 µg/dL] in stroke patients with normal serum creatinine levels in Taiwan [5,11,12]. Colleoni N et al and Kessler M et al, demonstrated elevated blood lead levels in patients who were on chronic renal dialysis [13,14]. A study which was done by Muntner P et al, demonstrated that there was an association between the blood lead level and the bone lead concentrations [15].…”
Section: Discussionmentioning
confidence: 92%
“…Blood lead levels depend on the content of lead in the soil and environment (consistent gradient from urban to suburban to rural areas). Concentrations of lead in blood and erythrocytes [8,19] are significantly increased in all patients with CRF [124], but they still remain within the accepted safe exposure range of !380 Ìg/l [118,125]. Blood lead levels and the cumulative lead excretion rates were significantly higher in gout patients with renal failure as compared to patients with normal renal function [126].…”
Section: Tin Strontium Rubidium Mercury Leadmentioning
confidence: 96%
“…Several studies have clearly demonstrated the cardiovascular, pulmonary, carcinogenic, and mortality risks of airborne PM 2.5 2833. Moreover, BLLs have been related to iPTH levels, hemoglobin levels, blood pressure, and mortality in patients on MHD 1,4,34,35. Whether BLL is an intermediate medium between airborne PM 2.5 and cardio vascular events or mortality in patients on MHD requires clarification in future studies.…”
Section: Discussionmentioning
confidence: 97%
“…However, in patients with renal failure, blood lead excretion is aggravated because of the loss of renal clearance. Therefore, patients on HD have significantly higher mean BLLs than healthy individuals 13. According to our review of the relevant literature, studies on particulate matter in terms of BLLs are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation